The construction workers in the Veja's magazine: some notes (Revista Angelus Novus, 2011)
Our work attempts to understand the class interests defended in the editorial line of Veja magazine, during the year 1968 is 1978, focusing on realizing the magazine as a private apparatus of hegemony to political affinities around a specific sector of the capital, firms construction. We intend to demonstrate how the magazine has built his speech in order to build consensus around the projects that this sector, we assume, were consistent with the magazine. Therefore, this article will seek to identify issues raised within that dealt with the construction industry, the figure of workers and how they are presented in Veja.